Intubation-Related Laryngeal Pathology Precluding Tracheostomy Decannulation: Incidence and Associated Risk Factors. (September 2021) - Meenan, Kirsten; Bhatnagar, Kavita; Guardiani, Elizabeth
Objectives: To identify the incidence and risk factors for intubation-related laryngeal lesions that preclude tracheostomy decannulation in a large population. Methods: A 3-year retrospective case-control study was performed of tracheotomized adults in acute rehabilitation facilities who underwent routine endoscopic evaluation of the airway as part of the facilities' decannulation protocol. Patients with known upper airway pathology, external laryngeal trauma, cricothyrotomy or emergent tracheostomy, prior head and neck radiation, isolated tracheal lesions, and patients with incomplete reports were excluded. The laryngeal pathologies were classified, and demographics and clinical features were compared between those whose lesions precluded decannulation and all other patients. Results: Three hundred seventy-one patients met inclusion criteria. One hundred six (28.6%) had laryngotracheal lesions. Forty-nine patients (13.2%) had intubation-related lesions of the larynx that precluded decannulation. These lesions included posterior glottic stenosis (30.6%), granulation tissue (24.5%), vocal fold immobility (16.3%), subglottic stenosis (16.3%), a combination of granulation tissue and stenosis (10.2%), and glottic edema (2.0%). A BMI ≥ 25 kg/m 2 was associated with laryngeal lesions precluding decannulation. There was no difference in age, sex, race, diabetes mellitus, endotracheal tube size, number of days intubated, and number of intubations between groups. Seventy-eight percent of patients with lesions precluding decannulation were decannulated after medical or surgical therapy. The decannulation rate of patients without lesions precluding decannulation was 79.9%. Conclusions: BMI ≥ 25 kg/m 2 may increase the risk of development of laryngeal lesions preventing decannulation. Given that 13.2% of tracheotomized patients have laryngeal lesions precluding decannulation, an endoscopic evaluation of the airway is important to prevent decannulation failure and future airway symptoms.